Comparative study on rapid composting of pure sugarcane trash and sugarcane trash-filter press mub combination. - Chu, Edgar R. Jr
A comparative study on the rapid composting (using Trichoderma harzianum) was done using (a) sugarcane trash-mudpress and (b) pure sugarcane trash as substrates. Results show that the sugarcane trash-mudpress decomposed faster, had higher phosphorus content, lower carbon content, and narrower carbon to ratio than the trash compost. Trash compost, on the other hand had high organic matter content. In comparison with commercial soil conditioner, the two composts have higher nitrogen and potassium content and is less expensive. Due to their high moisture content, the two would not qualify as organic fertilizers, but rather, as soil conditioner.